2023
DOI: 10.1007/s40258-023-00819-3
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Cost-Effectiveness Analyses of Colorectal Cancer Screening in Europe: Have Studies Included Optimal Screening Intensities?

Abstract: Objective To assess the range of strategies analysed in European cost-effectiveness analyses (CEAs) of colorectal cancer (CRC) screening with respect to the screening intervals, age ranges and test cut-offs used to define positivity, to examine how this might influence what strategies are found to be optimal, and compare them with the current screening policies with a focus on the screening interval. Methods We searched PubMed, Web of Science and Scopus for peer-reviewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 80 publications
(107 reference statements)
0
0
0
Order By: Relevance
“…In fact, aside from being cost-effective compared to no screening[ 23 ], a cost-effectiveness modeling study revealed that the number of gained life-years with a screening strategy involving annual FIT is comparable to that achieved with a colonoscopy every 10 years[ 47 ]. Annual screening is optimally cost-effective when using FIT[ 48 ]. Regarding detection of advanced adenomas, a systematic review and meta-analysis including thirty-one cross-sectional studies that utilized screening colonoscopy as the reference standard reported a sensitivity of 25%[ 49 ].…”
Section: Screening Optionsmentioning
confidence: 99%
“…In fact, aside from being cost-effective compared to no screening[ 23 ], a cost-effectiveness modeling study revealed that the number of gained life-years with a screening strategy involving annual FIT is comparable to that achieved with a colonoscopy every 10 years[ 47 ]. Annual screening is optimally cost-effective when using FIT[ 48 ]. Regarding detection of advanced adenomas, a systematic review and meta-analysis including thirty-one cross-sectional studies that utilized screening colonoscopy as the reference standard reported a sensitivity of 25%[ 49 ].…”
Section: Screening Optionsmentioning
confidence: 99%